ACA ethical standards casebooks - American Counseling Association; Herlihy, Barbara; Corey, Gerald (Alexandria, VA : American Counseling Association, 1996)
Perhaps the most basic function of a professional code of ethics is to educate members about sound ethical conduct. This casebook is designed to provide a foundation for analytic evaluation of the standards and guidance in applying ethical principles. It can be utilized in an ethics course or in a practicum or internship. The illustrative incidents clarify the intent of ethical standards and allow students a chance to discuss moral concerns. The book can also help experienced counselors. Following an introduction, the text is presented in four parts. Part 1 presents the American Counseling Association's code of ethics and standards of practice. These ethics are further explored in part 2 in which vignettes are used to illustrate such concerns as confidentiality, relationships, evaluation, teaching, research, and ethical resolutions. Part 3, through the use of 19 case studies, further explores the issues surrounding counseling ethics. The situations examined here include client rights and informed consent, ethics in multicultural counseling, confidentiality, competence, counseling minors, dual relationships, suicidal clients, counselor training, and the relationship between the law and ethics. A final section offers highlights of ethical practice. Appendices outline policies and procedures surrounding the interpretation and violation of ethics.
Includes bibliographical references
Keywords: American Counseling Association; Counseling -- Moral and ethical aspects -- United States; Counselors -- Professional ethics -- United States; Counseling -- Moral and ethical aspects -- United States -- Case studies; Counselors -- Professional ethics -- United States -- Case studies